Activated PI3Kinase Delta Syndrome—A Multifaceted Disease - Thouenon, Romane; Moreno-Corona, Nidia; Poggi, Lucie; Durandy, Anne; Kracker, Sven (Frontiers in Pediatrics, 2021)
Autosomal dominant gain-of-function mutations in the PIK3CD gene encoding the catalytic subunit p110δ of phosphoinositide 3-kinase-δ (PI3K-δ) or autosomal dominant loss-of-function mutations in the PIK3R1 gene encoding the p85α, p55α and p50α regulatory subunits cause Activated PI3-kinase-δ syndrome (APDS; referred as type 1 APDS and type 2 APDS, respectively). Consequences of these mutations are PI3K-δ hyperactivity. Clinical presentation described for both types of APDS patients is very variable, ranging from mild or asymptomatic features to profound combined immunodeficiency. Massive lymphoproliferation, bronchiectasis, increased susceptibility to bacterial and viral infections and, at a lesser extent, auto-immune manifestations and occurrence of cancer, especially B cell lymphoma, have been described for both types of APDS patients. Here, we review clinical presentation and treatment options as well as fundamental immunological and biological features associated to PI3K-δ increased signaling.